Comparative Study of Clinical, Pathological, Radiological, and Genetic Features of Patients With Adult Ocular Adnexal Xanthogranulomatous Disease, Erdheim-Chester Disease, and IgG4-Related Disease of the Orbit/Ocular Adnexa. Issue 2 (March 2017) - McKelvie, Penelope; McNab, Alan A.; Hardy, Thomas; Rathi, Vivek
Abstract : Purpose: To compare and contrast the clinical, radiologic, pathologic, and genetic features of patients with ocular adnexal IgG4-related disease (IgG4-RD) and patients with adult ocular adnexal xanthogranulomatous disease (XG). Methods: This retrospective review study identified patients with histological evidence of either disease from records of the pathology department of our hospital from 1996 to 2014. Clinical, imaging, and a variety of histopathologic features were collected for 23 patients with IgG4-RD and 13 patients with XG. Next generation sequencing with a 50-gene cancer screening panel was performed on biopsy tissues from 10 patients in each group. Results: Statistical differences between the 2 groups include eyelid (67%; p = 0.0002) and anterior orbital (75%; p = 0.0352) predilection for XG except for Erdheim-Chester disease subgroup which was more posterior and diffuse. Eyelid involvement was rare (4%) for IgG4-RD. Involvement of orbital nerves was seen in 30% of IgG4-RD and 0% in XG ( p = 0.0695). Five patients with IgG4-RD developed malignancy (4 lymphoma, 1 leiomyosarcoma), but none of XG patients. Discriminating pathological features were the presence of any IgG4+ plasma cells ( p = 0.0121) and the ratio of IgG4+/IgG+ plasma cells ( p =0.0294) for IgG4-RD. Five of 12 (42%) patients with XG had sufficient numbers of IgG4+ plasma cells/high power field to fulfill published diagnostic criteria for IgG4-RD, and 5 (42%) had a ratio of IgG4+/IgG+ plasma cells over 40%, but the numbers overall were less than seen in the IgG4-RD patients. The only genetic difference between the 2 groups was that BRAF V600E mutation was found in 1 of the 2 Erdheim-Chester disease patients, which form a subgroup of XG. Conclusions: IgG4-RD and XG share clinical, imaging, and histopathological features including IgG4+ plasma cells. Significant differences were the eyelid involvement in XG, orbital nerve involvement, and an elevated IgG4+/IgG+ ratio in IgG4-RD and the only genetic abnormality found was BRAF V600E mutation in the Erdheim-Chester disease subgroup of XG. Abstract : Clinical, pathological, radiological, and genetic features of patients with adult ocular adnexal xanthogranulomatous disease, Erdheim-Chester disease, and IgG4-related disease of the ocular adnexa are studied.